2021
DOI: 10.1007/s41347-021-00214-6
|View full text |Cite
|
Sign up to set email alerts
|

Freely Available Virtual Reality Experiences as Tools to Support Mental Health Therapy: a Systematic Scoping Review and Consensus Based Interdisciplinary Analysis

Abstract: The primary purpose of this article is to review the potential therapeutic value of freely available VR content as an addition to the practitioners ‘toolkit’. Research has shown that virtual reality (VR) may be useful to extend existing guided imagery-based practices found in traditional mental health therapy. However, the use of VR technology within routine mental health practice remains low, despite recent reductions in equipment costs. A systematic scoping review and interdisciplinary analysis of freely ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…It is important to note that while commercially available products (see Table 2) are developed with evidence-based principles in mind, most have not undergone, or are in the process of being tested for efficacy in randomized controlled trials (29). Similarly, freely available VR experiences are often marketed as having a mental health focus on open application marketplaces (e.g., SteamVR, Oculus), without verification of clinical utility or safety (63). Thus, there is a risk of unvalidated VR programs being marketed for both therapist-assisted or selfdirected therapy, with potential to cause harm to users and diminish the credibility of validated programs (9).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that while commercially available products (see Table 2) are developed with evidence-based principles in mind, most have not undergone, or are in the process of being tested for efficacy in randomized controlled trials (29). Similarly, freely available VR experiences are often marketed as having a mental health focus on open application marketplaces (e.g., SteamVR, Oculus), without verification of clinical utility or safety (63). Thus, there is a risk of unvalidated VR programs being marketed for both therapist-assisted or selfdirected therapy, with potential to cause harm to users and diminish the credibility of validated programs (9).…”
Section: Discussionmentioning
confidence: 99%
“…Social VR games can facilitate casual intimacy (Maloney and Freeman, 2020), which may provide opportunity for patients to engage with social phobias in low-stake settings. While most mental health VR apps have been rated unlikely to support patient care (Best et al, 2021), there is a growing abundance of other VR apps that may be useful in phobia and anxiety treatment protocols (Lindner et al, 2017). These commercial hardware, video games, and smartphone apps were not made for health purposes but there is ample opportunity to incorporate them into therapy today (Tuerk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This can make VR-based therapy feel disorienting, as people who provide and receive mental health care may not have extensive gaming experience (Tuena et al, 2020;Pimentel et al, 2021). A systematic review found 1,785 VR apps for mental health, but only 11 were rated as potentially beneficial for therapy due to poor functionality (Best et al, 2021). In addition to unintuitive design or lack of therapeutic customization, VR-related motion sickness (often called cybersickness or simulator sickness) remains an issue (Timothy .…”
Section: Barriers To Vret + Tmhmentioning
confidence: 99%
“…The questionnaire addressed the participant’s demographic profile and a series of Likert-scale statements using a seven-level scale (−3 = Strongly disagree or displeased to +3 = Strongly agree or pleased, and 0 = neutral). This approach was guided by Best et al’s (2021) [ 61 ] study, which used a similar questionnaire to collect data about how participants react to immersive experiences. The questionnaire also incorporated an open-ended question that allowed participants to express thoughts and justify answers.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to explore a virtual space and interact with objects within VR experiences has been shown to increase the level of immersion for users [ 38 , 39 , 61 ]. Mol (2019) [ 39 ] reported that older users were able to enjoy VR experiences more when they were able to independently explore the virtual environment by themselves instead of following predefined routes.…”
Section: Introductionmentioning
confidence: 99%